Performance of Two Novel Obesity Indicators for the Management of Metabolic Syndrome in Young Adults - Liu, Xiaoli; Ma, Chunpeng; Yin, Fuzai; Wang, Rui; Lu, Qiang; Lu, Na; Ma, Chunming (Frontiers in Endocrinology, 2021)
Background: MetS is a pathophysiological change based on the abnormal metabolism of many substances. The present study evaluated the performance of two novel obesity indicators, the visceral adiposity index (VAI) and lipid accumulation product (LAP), of metabolic syndrome (MetS) in young adults. Methods: A cross-sectional study was conducted on 448 young adults in Qinhuangdao. Receiver operating characteristic (ROC) curve analyses were performed to assess the accuracy of these two obesity indicators as diagnostic tests for MetS. Results: The prevalence of MetS was 2.0%. In the male subjects, LAP had the highest area under the ROC curve (AUC) value (AUC = 0.963), followed by VAI (AUC = 0.937). In the female subjects, LAP also had the highest AUC value (AUC = 0.931), followed by VAI (AUC = 0.861). However, there was no significant difference between the two obesity indicators (P > 0.05). Conclusion: The two obesity indicators were effective for the screening of MetS in young adults. LAP is the simpler of the two.